The effect of time of day on visual reaction time performance in boxers: evaluation in terms of chronotype - Kemal Kurak; İsmail İlbak; Stefan Stojanović; Ramazan Bayer; Yunus Emre İlbak; Krzysztof Kasicki; Tadeusz Ambroży; Łukasz Rydzik; Wojciech Czarny; Wojciech Czarny (Frontiers in Physiology)
IntroductionConsidering the impact of individual differences on athletes’ performance, chronotype emerges as a crucial variable in training program design. Chronotype influences an individual’s ability to achieve peak physical and cognitive performance at different times of the day based on their biological rhythms. While numerous studies have explored the relationship between chronotype and physical performance, its effect on reaction time performance remains insufficiently investigated. In sports, where reaction time is a key determinant—such as in boxing—understanding this relationship could contribute to the personalization of training programs. Therefore, the aim of this cross-sectional study was to examine how the visual reaction performance of active boxers varies at different times of the day based on their chronotypes.MethodsTwenty-four active boxers participated in the study. Their chronotypes were determined using the Morningness-Eveningness Questionnaire, categorizing them as either morning type (M-type) or evening type (E-type). The participants were divided into two groups: M-type (n = 12) and E-type (n = 12). Each participant completed a visual reaction time (VRT) performance test at three different times of the day: morning (09:00 h), afternoon (13:00 h), and evening (17:00 h).ResultsThe findings revealed a statistically significant group × time interaction effect on VRT performance (p < 0.01). M-type athletes showed a significant decline in VRT performance during the evening compared to the morning and afternoon. In contrast, E-type athletes demonstrated significantly better performance in the evening compared to the morning.ConclusionsBoxers’ visual reaction time performance varies throughout the day depending on their chronotype. These results suggest that coaches and exercise specialists should consider athletes’ chronotypes when designing training programs focused on reaction time enhancement. To optimize performance, it is recommended that M-type athletes conduct such training sessions in the morning, while E-type athletes should train in the evening, when their reaction time performance tends to peak.